2022
DOI: 10.1101/gr.276013.121
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation across 56,434 individuals in gnomAD

Abstract: Genomic databases of allele frequency are extremely helpful for evaluating clinical variants of unknown significance; however, until now, databases such as the Genome Aggregation Database (gnomAD) have focused on nuclear DNA and have ignored the mitochondrial genome (mtDNA). Here we present a pipeline to call mtDNA variants that addresses three technical challenges: (i) detecting homoplasmic and heteroplasmic variants, present respectively in all or a fraction of mtDNA molecules, (ii) circular mtDNA genome, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(136 citation statements)
references
References 62 publications
10
126
0
Order By: Relevance
“…We investigated different calculations for mtDNA-CN, and found that there was no significant difference between them. We demonstrate that we detect true population-level SNV variants at 2000× chrM coverage, as shown by our high overlap with variants in the gnomAD database ( 42 ). The most novel aspect of MitoHPC is the second iteration variant identification, which calls variants using a sample's unique chrM sequence as the reference.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We investigated different calculations for mtDNA-CN, and found that there was no significant difference between them. We demonstrate that we detect true population-level SNV variants at 2000× chrM coverage, as shown by our high overlap with variants in the gnomAD database ( 42 ). The most novel aspect of MitoHPC is the second iteration variant identification, which calls variants using a sample's unique chrM sequence as the reference.…”
Section: Discussionmentioning
confidence: 55%
“…To cross-validate the variants we identified, we determined how many of the variants were also present in the gnomAD v3 database of over 56 000 WGS samples ( 42 ). We took 8793 unique chrM homoplasmic and heteroplasmic variants from gnomAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, non-pathogenic polymorphic variants were identified in all samples mostly in homoplasmy or high-level heteroplasmy (>90%) along with variants of unknown significance which were observed mostly in low heteroplasmic frequency (<10%) (Supplementary Table 8). Assessing variant frequency within the general population and specific haplogroups is helpful when evaluating the pathogenicity of such variants 39 . The pathogenic variants identified by the Cas9-mtDNA-enrichment nanopore sequencing were compared with the clinical laboratory results.…”
Section: Resultsmentioning
confidence: 99%
“…variants that are present in a fraction of the mtDNA copies) is associated with aging as well as various diseases such as neurological and cardiovascular, cancer and diabetes ( Stewart and Chinnery, 2021 ). At the population level, Laricchia et al analyzed 56,434 mtDNA samples, where most samples showed no heteroplasmy; however, one in 250 samples carried pathogenic heteroplasmic variants above the 10% ( Laricchia et al, 2022 ). Bolze et al analyzed ∼200,000 mitochondrial genomes between 5% and 1% and identified one heteroplasmic variant per person on average (range from 0 to 13, median 0) ( Bolze et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%